The Effect of ChatGPT-Based Project-Based Learning Model and Digital Literacy on News Text Writing Skills - Mukhlis, Muhammad (Universitas Pendidikan Mandalika, 2024)
Through conventional learning, learning news text writing skills is still oriented towards completing tasks given by the teacher. In addition, the teacher's role in learning is more dominant so that students have very little opportunity to explore their abilities. The purpose of this study is to evaluate how project-based learning using ChatGPT and digital literacy affect students' learning outcomes related to news text writing skills. Furthermore, this study aims to investigate how digital literacy and the ChatGPT-based project-based learning model interact to influence news text writing skills. This study, which used an experimental design with an independent samples test and an ANOVA 2-way analysis, demonstrates that using the ChatGPT-based project-based learning model greatly enhances the capacity to produce news articles. The tcount value of 4.025 > ttable 1.672 and the sig value of 0.000 < 0.05, which indicate that Ha is accepted, support this. However, with the value of Fo(P*L) 0.248 and sig value 0.621 > 0.05, indicating that Ha is rejected, there is no interaction between the ChatGPT-based project-based learning model and digital literacy in influencing the capacity to create news material. The results of this test provide an assumption that between the ChatGPT-based project-based learning model and digital literacy skills do not jointly influence the learning outcomes of the ability to write news texts. This means that it is necessary to consider various factors that influence student learning success, both in the context of digital literacy and psychological factors that play an important role in the development of news text writing skills. This study adds significantly to our understanding of the efficacy and ramifications of the ChatGPT-based project-based learning model. It also emphasizes the significance of a comprehensive strategy for fostering students' news text writing abilities.